Trends in Roll-Your-Own Smoking: Findings from the ITC Four-Country Survey (2002–2008). (13th May 2012) - Young, David; Yong, Hua-Hie; Borland, Ron; Shahab, Lion; Hammond, David; Cummings, K. Michael; Wilson, Nick
Abstract : Objective . To establish the trends in prevalence, and correlates, of roll-your-own (RYO) use in Canada, USA, UK and Australia, 2002–2008. Methods . Participants were 19, 456 cigarette smokers interviewed during the longitudinal International Tobacco Control (ITC) Four-Country Survey in Canada, USA, UK, and Australia. Results . "Predominant" RYO use (i.e., >50 % of cigarettes smoked) increased significantly in the UK and USA as a proportion of all cigarette use (both P < .001 ) and in all countries as a proportion of any RYO use (all P < .010 ). Younger, financially stressed smokers are disproportionately contributing to "some" use (i.e., ≤50 % of cigarettes smoked). Relative cost was the major reason given for using RYO, and predominant RYO use is consistently and significantly associated with low income. Conclusions . RYO market trends reflect the price advantages accruing to RYO (a product of favourable taxation regimes in some jurisdictions reinforced by the enhanced control over the amount of tobacco used), especially following the impact of the Global Financial Crisis; the availability of competing low-cost alternatives to RYO; accessibility of duty-free RYO tobacco; and tobacco industry niche marketing strategies. If policy makers want to ensure that the RYO option does not inhibit the fight to end the tobacco epidemic, especially amongst the disadvantaged, they need to reduce the price advantage, target additional health messages at (young) RYO users, and challenge niche marketing of RYO by the industry.